Mutants of common bean alpha-amylase inhibitor-2 as an approach to investigate binding specificity to alpha-amylases - da Silva, Maria Cristina Mattar; Mello, Luciane Vieira; Coutinho, Marise Ventura; Rigden, Daniel Jonh; Neshich, Goran; Chrispeels, Maarten Jonh; Grossi-de-Sá, Maria Fátima (Pesquisa Agropecuaria Brasileira, 2004)
Despite the presence of a family of defense proteins, Phaseolus vulgaris can be attacked by bruchid insects resulting in serious damage to stored grains. The two distinct active forms of α-amylase inhibitors, α-AI1 and α-AI2, in P. vulgaris show different specificity toward α-amylases. Zabrotes subfasciatus α-amylase is inhibited by α-AI2 but not by α-AI1. In contrast, porcine α-amylase is inhibited by α-AI1 but not by α-AI2. The objective of this work was to understand the molecular basis of the specificity of two inhibitors in P. vulgaris (α-AI1 and α-AI2) in relation to α-amylases. Mutants of α-AI2 were made and expressed in tobacco plants. The exhibited activity toward the mammalian α-amylase. The replacement of His33 of α-AI2 with the α-AI1-like sequence Ser-Tyr-Asn abolished inhibition of Z. subfasciatus α-amylase. From structural modeling, the conclusion is that the size and complexity of the amylase-inhibitor interface explain why mutation of the N-terminal loop and resultant abolition of Z. subfasciatus α-amylase inhibition are not accompanied by gain of inhibitory activity against porcine α-amylase.